AB0776 Muscle ultrasonography: a potential new diagnostic tool for inflammatory myopathies. (12th June 2018) - Bhansing, K.; Saris, C.; Fransen, J.; van den Hoogen, F.; Verrips, A.; Cooper, R.; van Riel, P.; van Engelen, B.; Pillen, S.; Vonk, M.
Abstract : Background: Quantitative muscle ultrasound (QMUS) imaging has proven to be a useful, non-invasive technique to visualise normal and pathological skeletal muscle tissue. 1 Electromyography (EMG) findings are not always disease specific in patients suspected of idopathic inflammatory myopathies (IIM). Objectives: To assess diagnostic value of QMUS in patients suspected for an IIM and to compare results with EMG. Methods: In 57 patients, suspected for IIM, panel diagnosis blinded for QMUS was used as reference standard. QMUS results were used to classify patients according an ultrasound neuromuscular disorder (NMD) algorithm (normal/borderline/abnormal). The predictive value of QMUS and EMG was assessed in a two by two table and a multivariate logistic regression model. Results: Twenty-two patients (39%) were diagnosed with IIM; 8 polymyositis, 4 dermatomyositis, 4 necrotizing myopathy, 3 inclusion body myositis and 3 non-specific myositis. Sixteen patients were classified with other NMD. We found an increased echointensity of the sternocleidomastoid, biceps, forearm flexor and tibialis anterior in the IIM group. Sensitivity, specificity, positive and negative predictive values (PPV/NPV) were 82%, 51%, 51%, 82% for ultrasound NMD algorithm and 63%, 64%, 50%, 75% for EMG. Multivariate analyses showed area under the curve (AUC) (0.81) (0.69–0.92) for ultrasound NMD algorithm, EMG (0.79) (0.67–0.92) and ultrasound NMD algorithm plus EMG (0.82) (0.70–0.93). Conclusions: QMUS with NMD algorithm provides a fair diagnostic value for patients suspected for an IIM and is similar to EMG results. A sizeable NPV indicates a low rate of false negative QMUS results. In addition to the relevant PPV for the presence for NMD, QMUS could serve as a potential screening tool for clinicians to detect possible myopathies and to rule out the presence of IIM. References: [1] Zaidman CM, van Alfen N. Ultrasound in the Assessment of Myopathic Disorders. J Clin Neurophysiol. 2016;33(2):103–1 Disclosure of Interest: None declared